Bioequivalence of the Highest Dose Strength Fixed-Dose Combination Tablet Of Gemigliptin/Metformin Sustained Release (SR) and Individual Component Gemigliptin and Metformin XR Tablets in Healthy Subjects - Cho, Y.-S.; Lee, S. Hyang; Jung, J. Hyuk; Lim, H.-S.; Bae, K.-S. (Clinical therapeutics, 2017)
Background In type 2 diabetes mellitus, the combined use of agents with complementary mechanisms of action improves glucose control via correction of multiple pathophysiologic defects. Fixed-dose combination (FDC) therapy can offer not only these benefits, but also potentially increase patient compliance.